Coronary access following ACURATE neo implantation for transcatheter aortic valve-in-valve implantation: Ex vivo analysis in patient-specific anatomies - Arif A. Khokhar; Arif A. Khokhar; Francesco Ponticelli; Adriana Zlahoda-Huzior; Kailash Chandra; Rossella Ruggiero; Marco Toselli; Francesco Gallo; Alberto Cereda; Alessandro Sticchi; Alessandra Laricchia; Damiano Regazzoli; et al. (Frontiers in Cardiovascular Medicine, 2022)
BackgroundCoronary access after transcatheter aortic valve implantation (TAVI) with supra-annular self-expandable valves may be challenging or un-feasible. There is little data concerning coronary access following transcatheter aortic valve-in-valve implantation (ViV-TAVI) for degenerated surgical bioprosthesis.AimsTo evaluate the feasibility and challenge of coronary access after ViV-TAVI with the supra-annular self-expandable ACURATE neo valve.Materials and methodsSixteen patients underwent ViV-TAVI with the ACURATE neo valve. Post-procedural computed tomography (CT) was used to create 3D-printed life-sized patient-specific models for bench-testing of coronary cannulation. Primary endpoint was feasibility of diagnostic angiography and PCI. Secondary endpoints included incidence of challenging cannulation for both diagnostic catheters (DC) and guiding catheters (GC). The association between challenging cannulations with aortic and transcatheter/surgical valve geometry was evaluated using pre and post-procedural CT scans.ResultsDiagnostic angiography and PCI were feasible for 97 and 95% of models respectively. All non-feasible procedures occurred in ostia that underwent prophylactic “chimney” stenting. DC cannulation was challenging in 17% of models and was associated with a narrower SoV width (30 vs. 35 mm, p < 0.01), STJ width (28 vs. 32 mm, p < 0.05) and shorter STJ height (15 vs. 17 mm, p < 0.05). GC cannulation was challenging in 23% of models and was associated with narrower STJ width (28 vs. 32 mm, p < 0.05), smaller transcatheter-to-coronary distance (5 vs. 9.2 mm, p < 0.05) and a worse coronary-commissural overlap angle (14.3° vs. 25.6o, p < 0.01). Advanced techniques to achieve GC cannulation were required in 22/64 (34%) of cases.ConclusionIn this exploratory bench analysis, diagnostic angiography and PCI was feasible in almost all cases following ViV-TAVI with the ACURATE neo valve. Prophylactic coronary stenting, higher implantation, narrower aortic sinus dimensions and commissural misalignment were associated with an increased challenge of coronary cannulation.